(3efXheI aj GdYbGFOs - (3GdgePGfj, GdHZOGOj, GdfLaj, , TdjdI, YHO GdgGOj Hf LhGO Hf cGXe, J (B1333(3g`s ((3GdfLas)
(3ChdgG (B:s
(3hQHeG NdG Yf GdVOjf(B***(3eJUaG ajg HeG aj GdHjfs
(3BNQgG (B:s
(3YJQJg GdZQ eUGHjM GdXde(B***(3hef Hge JeJ Ydi GdNdb GdfYes
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe(B: (3L(B4(3, (B173s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
(3Qbej ZjQ edhfs
Keywords: (3GdJhMjO hGdedd hGdfMds